2011
DOI: 10.1002/eco.268
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes reveal linkages among ecohydrological processes in a seasonally dry tropical montane cloud forest

Abstract: Despite their critical role as freshwater resources and their vulnerability to anthropogenic pressures, our knowledge of the ecohydrology of tropical montane cloud forests remains limited. Here, we use a dual stable isotope approach (δ2H and δ18O) to trace water inputs, fluxes, and pools through a seasonally dry tropical montane cloud forest in central Veracruz, Mexico. We found strong seasonal variation in the isotope composition of precipitation inputs (δ2H ~130‰ and δ18O ~18‰), with significantly more deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
243
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(271 citation statements)
references
References 63 publications
22
243
1
5
Order By: Relevance
“…The seasonality of precipitation and its stable isotope signals and the seasonality of transpiration could produce different water pools (i.e. soil water vs. groundwater) with different isotopic characteristics, analogous to the findings of Brooks et al (2010) and Goldsmith et al (2012). Brooks et al (2010) found that evaporation changed stable isotope values of soil water.…”
Section: Effect Of Vegetation Cover and Topographymentioning
confidence: 55%
“…The seasonality of precipitation and its stable isotope signals and the seasonality of transpiration could produce different water pools (i.e. soil water vs. groundwater) with different isotopic characteristics, analogous to the findings of Brooks et al (2010) and Goldsmith et al (2012). Brooks et al (2010) found that evaporation changed stable isotope values of soil water.…”
Section: Effect Of Vegetation Cover and Topographymentioning
confidence: 55%
“…Ehleringer and Dawson, 1992;Dawson et al, 2002;Volkmann et al, 2016;Rothfuss and Javaux, 2017), and identifying plant water sources (e.g. Brooks et al, 2010;Dawson and Ehleringer, 1991;Dawson and Simonin, 2011;Goldsmith et al, 2012;Evaristo et al, 2015;Hervé-Fernández et al, 2016;McCutcheon et al, 2017). A recent review by Sprenger et al (2016) 5 provides an extensive overview of isotope-based studies in the unsaturated zone.…”
mentioning
confidence: 99%
“…To detect whether isotopic variations occurred between different rain events during the study period (as reported in tropical forest elsewhere (Goldsmith et al, 2012)), rain samples were taken twice, at the 15th of September and at the 5th of October. No isotopic variations were observed between the two samples.…”
mentioning
confidence: 99%